First mitochondrial genome of the Amazonian marsh rat Holochilus sciureus Wagner 1842 (Rodentia, Cricetidae, Sigmodontinae) - Susette Castañeda-Rico; Jesús E. Maldonado; Robert C. Dowler; Cody W. Edwards (Mitochondrial DNA. Part B. Resources, 2022)
The Amazonian marsh rat, Holochilus sciureus, is a member of the subfamily Sigmodontinae, the second-largest subfamily of muroid rodents, with 410 species and ca. 84 genera in 12 tribes. This semiaquatic rodent is distributed in South America and is of great economic and epidemiological importance. In this study, we obtained the first mitochondrial genome of the genus Holochilus obtained from a tissue sample associated with a museum voucher specimen. The generated mitogenome sequence of H. sciureus is 16,358 bp length. It comprises a control region and a conserved set of 37 genes encoding for 2 rRNA genes, 22 tRNA genes and 13 protein-coding genes. We conducted a phylogenetic analysis that included H. sciureus and the only five other published mitochondrial genomes of this poorly studied subfamily of rodents.